The Sanctity of human life. A perspective from New Testament anthropology - Zyl, Hermie C. van (Verbum et ecclesia, 1993)
The article deals with sanctity of life issues such as abortion, euthanasia, treatment of the disabled, war, and capital punishment. These matters are not treated individually but collectively from the perspective of New Testament anthropology. Having taken care of a few methodological considerations, the main focus falls on a discussion of man as sinner, man in Christ, and the category of the least.